Improving the production of micafungin precursor FR901379 in Coleophoma empetri using heavy-ion irradiation and its mechanism analysis - Yongjuan Liu; Beibei Wang; Xiaoxi Zhang; Ping Men; Meng Gu; Yu Zhou; Wei Hu; Zhuanzi Wang; Min Wang; Xuenian Huang; Xuefeng Lu (Mycology)
Micafungin is a semisynthetic echinocandin antifungal agent derived from fungal natural product FR901379 produced by Coleophoma empetri, facing challenges in biomanufacturing due to poor chassis performance and unclear high-yield mechanisms. In this study, the mutagenic effects of heavy-ion beam and how fungi repaired damage show that compared to the wild-type strain, nonhomologous end-joining pathway deficient mutants were more sensitive to heavy ion radiation, resulting in higher lethality rates and more mutations from the same radiation dose. Moreover, mutants obtained through two rounds of heavy-ion irradiation mutagenesis produced 1.1 g/L of FR901379, representing a remarkable increase of 253.7%. Compared to the parent strain, the mutants displayed noticeable differences in morphology and fermentation status. Comparative genomic analysis revealed mutations in several genes critical for morphological differentiation, which may have enhanced the production of FR901379 in the excellent mutants. This study has implications for the application of heavy-ion irradiation to filamentous fungi breeding. Additionally, the mutants with high FR901379 titre not only improve the production efficiency of micafungin but also provide a better chassis and theoretical guidance for subsequent metabolic engineering.